e-UNNAT and Public Service Guarantee Act 2011: Driving Reform in Jammu and Kashmir - Shafi, Muzamil; Singh, Manvendra (Journal of Neonatal Surgery, 2025)
This paper explores the shift towards e-governance in Jammu and Kashmir (J&K) under the Digital India program, focusing on platforms like Jansugam.jk.gov.in and state.ras.gov.in. These initiatives aim to enhance administrative efficiency and citizen engagement by utilizing Low Code–No Code (LCNC) architecture, facilitating user-friendly service delivery. The Rapid Assessment System (RAS) further improves service quality by incorporating feedback and role-based access control. The e-UNNAT portal, consolidating over 1050 services, exemplifies the region's move to streamline service delivery, while the Public Services Guarantee Act’s auto-appeal system ensures timely service and accountability. Despite these advancements, challenges remain, including linguistic diversity, trust in technology, geographical barriers, and digital inequality, particularly in rural areas. This paper proposes a unique model to address these challenges, focusing on localized digital literacy campaigns, multilingual support, and community-based tech support networks. The model also emphasizes infrastructure development in underserved regions to bridge the digital divide. Overcoming these barriers is essential to ensure inclusive, effective e-governance and equitable access to public services in Jammu and Kashmir, ultimately improving governance and citizen satisfaction.